(untitled) (ADMPG Journal, 2021)
Incubators play a fundamental role in economic and social generation in the region where they are located. The development of incubators promotes the survival and maturation of small and medium enterprises. These types of companies are essential for generating employment and local income and contribute to our country’s GDP. Being an entrepreneur is something difficult and requires a lot of work and study, it is not enough just will, incubators help in this development process. 2020 was a challenging year for all small and medium businesses that were most affected by the pandemic. The purpose of this article is to present the implications of the sanitary/economic crisis in incubators in the state of Paraná during the year 2020. Identifying which impacts were felt and which alternatives were taken to provide assistance to member companies. This study fits into the following research methods: qualitative, of an applied nature, as to the objectives being exploratory and descriptive, and as to the procedures, a survey was carried out. A questionnaire consisting of 19 questions was used, divided into two parts: the first a description of the profile and characteristics of the incubators, and the second part with the impacts of the pandemic. It concludes the importance of evaluating the impact on activities, services offered and in the financial area, suffered by incubators during this period of pandemic, where significant changes were felt by all segments of the world economy.